Informal Food Retail Trade in Nigeria's Secondary Cities - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This data is from a study conducted on informal food retail in two of Nigeria’s secondary cities, Calabar and Minna. The aim of the survey is to gather information on the livelihoods of these traders and the governance constraints they encounter outside of the region’s capital and primate cities. Interviews with 1,097 informal food vendors – 530 in Calabar and 567 in Minna – across nine markets in each city, allow for a better understanding of the role of informal food vendors in secondary cities as a key component of agricultural transformation and food security, while also examining how their treatment by government officials affects their own food security and their ability to facilitate agricultural transformation. The survey is split into 11 survey modules: 1. Sampling (SA) – preliminary characteristics of the informal food trader 2. General Information (ID) – basic demographic, educational and household background information 3. Employment (EM) – details on current job 4. Business (BS) – information on business management and the associated fees paid to operate 5. Taxes and Fees (TX) – range of fees and taxes paid and the benefits received from those payments 6. Government Engagement (GE) – type and level of interaction between government officials and food traders 7. Food Safety and Food Security (FS) – awareness of food safety and source of personal food 8. Service Delivery and Accountability (SD) – services offered in the market and who could best deliver them 9. Public Participation and Associational Membership (PP) – involvement in different associations and participation in public and community affairs 10. Household Welfare (HW) – details on household assets and services 11. Final (FI) – enumerator observations